High-throughput, outdoor characterization of photovoltaic modules by moving electroluminescence measurements - Doll, Bernd; Pickel, Tobias; Schreer, Oliver; Zetzmann, Cornelia; Hepp, Johannes; Teubner, Janine; Buerhop, Claudia; Hauch, Jens; Camus, Christian; Brabec, Christoph (Optical Engineering, 2019)
Fast and nondestructive quality control tools are important to assess the reliability of photovoltaic plants. On-site inspection is essential to minimize the risk of further damage and electrical yield losses. The most effective way of achieving this is with highly sensitive imaging techniques such as luminescence or infrared thermography imaging. Nowadays, electroluminescence (EL) is used at nighttime to detect defects such as local cell changes, series resistances, and shunts. However, the drawback of this method is low measurement throughput. To increase the throughput, indium gallium arsenide detectors with a resolution of 640 × 512 pixels are used, for which short integration times are possible to acquire EL images. For such short integration times, even moving image acquisition and movie recording are feasible to detect the mentioned defects. An outdoor EL setup is presented for mobile handheld recording, which can even be used under low-light conditions, below 100 W / m2, at daytime. Experiments show that 5 ms integration time is a good compromise between low contrasts for lower integration times and motion blur for higher integration times. The camera prototype has an onboard computer to avoid image transmission losses and an external lithium polymer battery power supply for improved mobility.
CRIS-Team Scopus Importer:2019-09-27
Keywords: defect detection; electroluminescence; high throughput; indium gallium arsenide camera; on-site inspection; photovoltaic module